ANALISIS PENYERAPAN TENAGA KERJA LULUSAN SEKOLAH MENENGAH KEJURUAN PADA LAPANGAN KERJA DI PROVINSI SULAWESI TENGGARA - Marlina, Marlina; Harafah, La Ode Muh.; Rosnawintang, Rosnawintang (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to determine and analyze the employment of vocational school graduates in Southeast Sulawesi Province by field of expertise and employment. The object of this research is vocational high school graduates in Southeast Sulawesi Province. The type of data used in this research is secondary data. Secondary data were obtained from BPS Southeast Sulawesi, Education Office of Southeast Sulawesi, Special Job Exchange of Southeast Sulawesi Province and the Office of Manpower and Industry of Southeast Sulawesi Province. The data analysis method used is descriptive analysisThe results of this study indicate that the areas of expertise in Technology and Engineering, Information and Communication Engineering, Business and Management, Tourism, and Arts and Creative Industries are areas of expertise that are mostly absorbed in the employment sector, namely the trade sector, each with 4.56% Technology and Engineering, 7.98 % Information and Communication Engineering, 9.63% Business and Management, 7.63% Tourism, and 6.8% Industrial and Creative Arts. For the field of expertise, Energy and Mining is mostly absorbed in the mining sector, which is 15.72%. The areas of expertise in Health and Social Workers are mostly absorbed in the service sector, namely 4.71%. The fields of expertise in Agribusiness and Agrotechnology and the areas of expertise in Maritime were most absorbed in the Agriculture sector, with 5.18% and 14.35% respectively. On the other hand, the employment of SMK graduates in Southeast Sulawesi Province is employment with a percentage of 0% Keywords: SMK graduates; Areas of expertise; Jobs.